Use of hyaluronic acid in facial harmonization procedures by aesthetic pharmacist: an integrative review (Research, Society and Development, 2022)
The present study aims to report the action of hyaluronic acid as a function of the size of the molecule, its functions, highlight its physicochemical aspects, the pharmaceutical forms found on the market, as well as list the facial harmonization techniques in which the aesthetic pharmacist can accomplish. To this end, an integrative literature review was conducted with articles published from 2017 to 2021, indexed in the databases of PubMed, Google Scholar, SciELO, Libraries of Brazilian Federal Universities from the descriptors: aesthetics, hyaluronic acid, harmonization, facial filling, pharmaceutical. 37 articles were used in which they demonstrated that the particle size and the degree of reticulation of hyaluronic acid can be crucial in skin permeation, this can be found in several pharmaceutical forms as in dermo cosmetics whose action would be topical and in the aesthetic area the injectables are used for filling, giving volume, hydration and even favoring collagen production. It can be concluded that ha injectable gel is the pharmaceutical form used for facial harmonization and the process of crosslinking of this molecule is of paramount importance, because it generates a product with more stability and clinical time to the patient and that the pharmacist is one of the qualified professionals who ensures that the procedure is performed safely.